2021
DOI: 10.1007/s10800-021-01596-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precursor particle size and morphology on lithiation of Ni0.6Mn0.2Co0.2(OH)2

Abstract: In this paper, Ni0.6Mn0.2Co0.2(OH)2 precursors with several different morphologies and particle sizes are mixed with Li2CO3 and heat treated for 5, 7.5 and 10 h. The effects of the precursor properties on the degree of lithiation, electrochemical properties and volumetric capacities of lithiated product are compared. Based on the characterization results, a small (3 μm), narrow span precursor can be lithiated in a short period of time (5 h) and has good initial discharge capacity (185 mA h g− 1) and capacity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…As seen in Figure S7, the broadest particle size distribution was observed for the MW_60m_A sample. It may result in uneven charging of particles of different sizes and finally promote the structural collapse of the biggest ones [29]. Hence, we considered the prolonged microwave treatment as not favorable for obtaining the particles with a sufficiently narrow size distribution that compromises the capacity retention.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Figure S7, the broadest particle size distribution was observed for the MW_60m_A sample. It may result in uneven charging of particles of different sizes and finally promote the structural collapse of the biggest ones [29]. Hence, we considered the prolonged microwave treatment as not favorable for obtaining the particles with a sufficiently narrow size distribution that compromises the capacity retention.…”
Section: Resultsmentioning
confidence: 99%
“…In application, the spent NMC111 could introduce many challenges including the heterogeneity in chemical composition, particle and morphology breakdown, wide particle size distribution, and contamination with impurities from the recycling process. All these could affect the material performance and need to be restored [33,34]. Much more work is required to further validate the viability of the method for practical application.…”
Section: Discussionmentioning
confidence: 99%
“…19 High residual lithium amount in the cathode is known to introduce reactions with the electrolyte and produce gases, leading to a poor contact inside the battery cell [20][21][22] . In another study 23 , effect of washing was evaluated over NCM622 cathode active materials. It was observed that water has detrimental effect on the cathode surface structure, which was seen as decreased cycle retention after the washing 24,25 .…”
Section: Huang Et Al (2015)mentioning
confidence: 99%